Conversation with Rafael Moneo - Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
Rafael Moneo has just opened an exhibition at the headquarters of the Barrié Foundation in La Coruña which contains an important sample of his work as an architect from 1962 to date. The exhibition documents  fifty years of  uninterrupted  work,  filtered  through  the  leitmotif  of some drawings which reveal the importance for Moneo of representing architecture as a design tool. Between the neat lines of these drawings we can also learn the trends which architectural culture has followed in the second half of the 20th century, and how it has evolved in architects’ hands.